Synthesis, characterization and cytotoxicity evaluation of magnetic nanosilica in L929 cell line - Bruckmann, Franciele da Silva; Pimentel, Amanda Carolina; Viana, Altevir Rossato; Salles, Theodoro da Rosa; Krause, Luciana Maria Fontanari; Mortari, Sérgio Roberto; Silva, Ivana Zanella da; Bohn Rhoden, Cristiano Rodrigo (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
Recently, the incorporation of magnetic nanoparticles in nanomaterials has been showning to be very efficient, which leads to several scientific studies being carried out. Magnetic silica nanoparticles have excellent properties, enabling application in different fields including nanoscience. In this context, this work aimed to synthesize and characterize nanosilica with magnetic properties, in order to evaluate of the cytotoxicity in L929 cell line. The methodology for incorporation of magnetic nanoparticles proved to be fast and effective for obtaining the magnetic nanosilica (Nano SiO2.Fe3O4). Through the characterization of FTIR, and exposure of the magnetic field it was possible to verify the incorporation of ferrite in the nanosilica, as well as the XRD technique, the reduction of the particle size and the degree of crystallinity was evidenced. It was possible to verify that the synthesized nano SiO2.Fe3O4 showed to be safe in the treatments with lower concentrations with less amount of incoporated ferrite. Nevertheless, more characterizations and studies will be developed to determine the safety and therapeutic efficacy of this magnetic nanoparticles.